Immediate Psychological Effects of the COVID-19 Quarantine in Youth From Italy and Spain - Orgilés, Mireia; Morales, Alexandra; Delvecchio, Elisa; Mazzeschi, Claudia; Espada, José P. (Frontiers in Psychology, 2020)
The COVID-19 quarantine has affected more than 860 million children and adolescents worldwide but, to date, no study has been developed within Western countries to examine the psychological impact on their lives. The present study aims to examine for the first time the emotional impact of the quarantine on children and adolescents from Italy and Spain, two of the most affected countries by COVID-19. Participants were 1,143 parents of Italian and Spanish children aged 3 to 18 years who completed a survey providing information about how the quarantine affects their children and themselves, compared to before the home confinement. Results show that the 85.7% of the parents perceived changes in their children´s emotional state and behaviors during the quarantine. The most frequent symptoms were difficulty concentrating (76.6%), boredom (52%), irritability (39%), restlessness (38.8%), nervousness (38%), feelings of loneliness (31.3%), uneasiness (30.4%), and worries (30.1%). Spanish parents reported more symptoms than Italians. As expected, children of both countries used monitors more frequently, spent less time doing physical activity, and slept more hours during the quarantine. Furthermore, when family coexistence during quarantine became more difficult, the situation was more serious, and the level of stress was higher, parents tended to report more emotional problems in their children. The quarantine impacts considerably on Italian and Spanish youth, reinforcing the need to detect children with problems as early as possible to improve their psychological well-being.